Evolution of Pathology Patterns in Persons Who Died From COVID-19 in Italy: A National Study Based on Death Certificates - Grippo, Francesco; Grande, Enrico; Maraschini, Alice; Navarra, Simone; Pappagallo, Marilena; Marchetti, Stefano; Crialesi, Roberta; Frova, Luisa; Orsi, Chiara; Simeoni, Silvia; Carinci, Annamaria; Loreto, Giuseppe; et al. (Frontiers in Medicine, 2021)
Background: In Italy, during the first epidemic wave of 2020, the peak of coronavirus disease 2019 (COVID-19) mortality was reached at the end of March. Afterward, a progressive reduction was observed until much lower figures were reached during the summer, resulting from the contained circulation of SARS-CoV-2. This study aimed to determine if and how the pathological patterns of the individuals deceased from COVID-19 changed during the phases of epidemic waves in terms of: i) main cause of death, ii) comorbidities, and iii) complications related to death. Methods: Death certificates of persons who died and tested positive for SARS-CoV-2, provided by the National Surveillance system, were coded according to ICD rev10. Deaths due to COVID-19 were defined as those in which COVID-19 was the underlying cause of death. Results: The percentage of COVID-19 deaths varied over time. It decreased in the downward phase of the epidemic curve (76.6% versus 88.7%). In February–April 2020, hypertensive heart disease was mentioned as a comorbidity in 18.5% of death certificates, followed by diabetes (15.9% of cases), ischemic heart disease (13.1%), and neoplasms (12.1%). In May–September, the most frequent comorbidity was neoplasms (17.3% of cases), followed by hypertensive heart disease (14.9%), diabetes (14.8%), and dementia/Alzheimer’s disease (11.9%). The most mentioned complications in both periods were pneumonia and respiratory failure with a frequency far higher than any other condition (78.4% in February–April 2020 and 63.7% in May–September 2020). Discussion: The age of patients dying from COVID-19 and their disease burden increased in the May–September 2020 period. A more serious disease burden was observed in this period, with a significantly higher frequency of chronic pathologies. Our study suggests better control of the virus’ lethality in the second phase of the epidemic, when the health system was less burdened. Moreover, COVID-19 care protocols had been created in hospitals, and knowledge about the diagnosis and treatment of COVID-19 had improved, potentially leading to more accurate diagnosis and better treatment. All these factors may have improved survival in patients with COVID-19 and led to a shift in mortality to older, more vulnerable, and complex patients.